Pengaruh Service Quality, Brand Image, Customer Satisfaction, dan Custom Er Trust dalam Membentuk Customer Loyalty pada Pelanggan Brand Kecantikan Ramah Lingkungan di Wilayah DKI Jakarta - Sintya, Lisna; Suhud, Usep; Bara Berutu, Meta (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to determine the effect of: 1) service quality on brand image. 2) service quality on customer satisfaction. 3) service quality on customer trust. 4) brand image on customer loyalty. 5) customer satisfaction on customer loyalty. 6) customer trust on customer loyalty. Data was collected by questionnaires distributed online through social media. Respondents in this study are those who live in the DKI Jakarta Region, are 18-55 years old and have purchased Sensatia Botanicals products within the past year. This study uses SPSS version 25 and AMOS version 25 software to analyze data. The results of this study indicate that all hypotheses have a positive and significant effect. The results of this study indicate that service quality has a positive and significant effect on brand image, service quality has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer trust, brand image has a positive and significant effect on customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty, and customer trust has a positive and significant effect on customer loyalty.